STRATEGI MENINGKATKAN KUALITAS PEMBELAJARAN MELALUI LESSON STUDY - Parmin, - (Lembaran Ilmu Kependidikan, 2007)
No one ever knows the learning processes in a classroom but the teacher. Thelearning quality improvement is the responsibility of not only the teacher but also allcomponents of an education institution either a school or university. In order to gain acollegial relationship among the components, a Lesson study can be implemented. Thesteps of a Lesson study include planning, doing, and reflecting. Through Lesson study,it is very likely that knowledge sharing occurs. Through a constructive developmentof knowledge, learning innovation can emerge and educators will have the opportunityto improve the teaching quality.Kata kunci: kualitas pembelajaran, lesson study